A New Class of Dual-mode Substrate Integrated Waveguide (SIW) Filter with Two Metalized Posts - Zakaria, Z; Sam , W. Y; Abd Aziz, M. Z. A; Mutalib , M. A; Md Saat, M. S (2013)
This paper presents the investigation and characterization of dual-mode Substrate Integrated Waveguide (SIW) filter with two metalized posts on the cavity to reduce the overall volume of RF front-end subsystems. By introducing two vertical metalized posts and two diagonal metalized posts in dual-mode SIW filter, both SIW filters show different flow of Electromagnetics (EM) can be identify from the E-fields. In order to compare which dual-mode SIW filter gives the better performance, the designs are simulated at centre frequency 2 GHz using CST Studio Suite software and the results are validate through measurement. The measurement shows a good agreement with the simulated results. This design is suitable for any integration microwave system where the reduced complexity of the design and cost as well as weight is very important for the wireless communication systems.